School-based screening for childhood anxiety problems and intervention delivery: a codesign approach - Tamsin Ford; Alastair Gray; Cathy Creswell; Victoria Williamson; Obioha Ukoumunne; Falko Sniehotta; Mara Violato; Ian McDonald; Paul Brown; Paul Stallard; Michael Larkin; Tessa Reardon; et al. (BMJ Open)
Objectives A very small proportion of children with anxiety problems receive evidence-based treatment. Barriers to access include difficulties with problem identification, concerns about stigma and a lack of clarity about how to access specialist services and their limited availability. A school-based programme that integrates screening to identify those children who are most likely to be experiencing anxiety problems with the offer of intervention has the potential to overcome many of these barriers. This article is a process-based account of how we used codesign to develop a primary school-based screening and intervention programme for child anxiety problems.Design Codesign.Setting UK primary schools.Participants Data were collected from year 4 children (aged 8–9 years), parents, school staff and mental health practitioners.Results We report how the developed programme was experienced and perceived by a range of users, including parents, children, school staff and mental health practitioners, as well as how the programme was adapted following user feedback.Conclusions We reflect on the mitigation techniques we employed, the lessons learnt from the codesign process and give recommendations that may inform the development and implementation of future school-based screening and intervention programmes.